Demographic determinants of happiness in Andalusia: insights from the 2022 social survey data - Matas-Terrón, Antonio; Sánchez Barroso, Carmen; Matas-Terrón, José M. (Frontiers in Public Health, 2024)
The Social Survey of Andalusia is an instrument for monitoring the Andalusian reality developed by the regional government of Andalusia, whose dataset is open access to the citizens. The 2022 edition included questions related to happiness, social relations as well as socio-demographic factors. Based on this dataset, the present study aimed to analyse the relationship between socio-demographic factors and people’s experiences of happiness. It also set out to explore which factors might be indispensable for experiencing moments of happiness as measured in the survey. A sample of 4,968 cases was gotten, conducting a descriptive analysis, a logit regression in complex samples, and a Necessary Conditions Analysis. The results found two very different social profiles in terms of the experience of happiness, determined by age, sex, educational level and economic status. However, neither factor proved to be a necessary condition for happiness. Both conclusions should be taken into consideration in any socio-community intervention.